2015
DOI: 10.3109/14992027.2014.989455
|View full text |Cite
|
Sign up to set email alerts
|

Speech perception with F0mod, a cochlear implant pitch coding strategy

Abstract: D espite technological advances employed in signal processing strategies, one of the remaining obstacles are spectral gap details on the information transmitted. Considering its importance in speech perception, researchers have investigated mechanisms to optimize spectral details through virtual spectral channels. The clinical application of this technique resulted in a new approach to signal processing-the HiRes 120. Objective: To assess the auditory performance of cochlear implant users with the HiRes 120 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…This conjecture is supported by results of an earlier study with adult CI recipients which demonstrated that English sentence perception using eTone in moderate-levels of noise was comparable to that of ACE (Vandali & van Hoesel, 2012). Similar outcomes were observed by Francart et al (2015) for Flemish sentence perception using F0mod and ACE. However, in the present study, Mandarin sentence perception is also dependent to some extent on lexical tone recognition, and so we cannot rule out the possibility that any improvement in lexical tone perception in the SRT test may have balanced deficits in coding of segmental speech information, or did not directly translate to similar levels of improvement in the sentence tests (the latter perhaps due to the strong dependency of contextual information in sentence perception).…”
Section: Sentence Perception In Noisesupporting
confidence: 86%
“…This conjecture is supported by results of an earlier study with adult CI recipients which demonstrated that English sentence perception using eTone in moderate-levels of noise was comparable to that of ACE (Vandali & van Hoesel, 2012). Similar outcomes were observed by Francart et al (2015) for Flemish sentence perception using F0mod and ACE. However, in the present study, Mandarin sentence perception is also dependent to some extent on lexical tone recognition, and so we cannot rule out the possibility that any improvement in lexical tone perception in the SRT test may have balanced deficits in coding of segmental speech information, or did not directly translate to similar levels of improvement in the sentence tests (the latter perhaps due to the strong dependency of contextual information in sentence perception).…”
Section: Sentence Perception In Noisesupporting
confidence: 86%
“…27 Furthermore, Francart et al recently demonstrated that another fundamental frequency modulation (F0mod) processing strategy improves pitch perception, pitch ranking, and familiar melody identification without interfering with speech recognition. 28 These frequency manipulation studies suggest that reduction of higher harmonics might also be incorporated into future CI coding strategies to further improve music perception and enjoyment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, speech understanding by CI users can be improved by strategies that mimic adaptation, thereby enhancing slow speech modulations and the onsets and (for some strategies) offsets of sounds (Azadpour and Smith, 2016;Geurts and Wouters, 1999;Koning and Wouters, 2016). Similarly, improvements in pitch perception and, in some instances, speech intelligibility, have been obtained with strategies that enhance modulation coding such as F0Mod (Francart et al, 2015;Laneau et al, 2006) and eTone van Hoesel, 2012, 2011), or that combine amplitude and rate modulation, like the ARTmod strategy (Brochier et al, 2018). For the latter, speech signals are encoded by using both amplitude and rate modulation simultaneously to enhance the temporal envelope.…”
Section: Subject Variability and Comparison To Other Strategiesmentioning
confidence: 99%
“…Thus, fluctuating masker types will lead to more complex spectral and temporal variations in SNR which may reduce or compromise the potential benefit of removing low-amplitude pulses. Further, the envelope contrast enhancements that occur with TIPS might, as with other strategies that enhance envelopes, lead to benefits in pitch or ITD coding (Francart et al, 2015;Laneau et al, 2006;Smith et al, 2013). Thus, the effect of TIPS on performance in those tasks should be considered for future evaluation.…”
Section: Perspectivesmentioning
confidence: 99%